Understanding drivers of food choice in low- and middle-income countries: A systematic mapping study - Karanja, A.; Ickowitz, A.; Stadlmayr, B.; McMullin, S. (Elsevier, 2022)
Understanding individual-based motives governing food choice is necessary to design appropriate interventions and support food systems consistent with consumer characteristics, preferences and values. We used a systematic mapping approach to identify and systematize available evidence on drivers of food choice in low- and middle-income countries. We identified a list of forty (40) individual-based motives which were sorted into seven (7) clusters with a focus on health and nutrition perceptions, psychological factors, sociocultural factors, sensory appeal, social interactions, socio-demographic variables, and ethical concerns. We mapped the clusters and dimensions of the food environment, as well as the geographical locations of the reviewed studies. Most studies focused on adults and women in particular, especially those investigating the role of cultural-based food taboos and diet restrictions. Studies related to the dimensions of the food environment focused on food affordability, convenience, food availability and promotional information. Sub-Saharan Africa was the most studied region for understanding drivers of food choice followed by East Asia and Pacific and South Asia. Heatmaps of the current evidence across rural-urban landscapes revealed that existing studies are skewed towards urban settings with a dearth of studies in rural and peri-urban contexts. Based on our review, we highlight areas for future research such as food safety and ethical concerns for environmental sustainability, food waste, and animal welfare. There is a need for systemic research frameworks that contextually appreciate rural-urban and consumer-producer linkages, to inform a leverage point for more targeted interventions in promotion of healthier diets.